The Settlement of Abuse of Authority by Government Officials - Puhi, Oyaldi; Akili, Rustam Hs; Moonti, Roy Marthen (Faculty of Law Universitas Negeri Semarang, 2020)
This paper discusses the main problems in handling disputes over the abuse of authority by state officials. This paper is based on the concept of the state as an organization or the highest body that has the authority to regulate matters relating to the interests of the wider community and has the obligation to prosper, protect and educate the life of the nation. This paper aims to analyze the Authority of Government Officials in carrying out Government and the Settlement of Abuse of Authority within the scope of Government Officials. This paper confirms that the issuance of Law Number 30 of 2014 concerning Government Administration is a response and response to the polemic surrounding which judicial institution has the competence to examine whether or not there is an alleged element of abuse of authority by a public official. The law expressly mandates the state administrative court as a judicial institution that has absolute competence to examine the alleged abuse of authority. The presence or absence of an element of abuse of authority must be tested with the principle of specialism (specialiteitsbeginsel) which is nothing but the domain of administrative law. The Decision of the State Administrative Court in resolving the abuse of authority carried out by the Agency and / or Government Official that harms the state finances as stipulated in Law No. 30 of 2014, has binding legal force and must be obeyed and implemented by the relevant Government Officials.